Research progress of Baduanjin in exercise rehabilitation for elderly patients with stable angina pectoris of coronary heart disease (八段锦在老年冠心病稳定型心绞痛患者运动康复中应用的研究进展) - HAN Ruishu (韩睿书); SUN Yunhua (孙云华); WANG Jinfeng (王金凤); WANG Wei (王玮) (Journal of International Translational Medicine Limited, 2022)
This paper gave a brief introduction about the exercise prescription and Traditional Chinese Medicine exercise therapy in the cardiac rehabilitation for elderly patients with coronary heart disease. A summary of implementation method and evaluation index of Baduanjin exercise and review of the studies about intervention effect of Baduanjin were provided, in order to provide reference for cardiac rehabilitation of elderly patients with stable angina pectoris of coronary heart disease. (本文简要阐述了运动处方和中医运动疗法在冠心病患者心脏康复中的运用现状, 总结八段锦运动干预方法和评价指标, 对老年冠心病稳定型心绞痛患者八段锦运动疗法干预效果的研究进行综述, 以期为老年冠心病稳定型心绞痛患者应用八段锦进行运动干预提供借鉴。)